Wanita di Antara Perubahan: Proses Adaptasi Sosial Warga Binaan Lapas Perempuan Kelas IIA Semarang - Nahwa Cika Rialida; Suyanto Suyanto; Vania Pramudita Hanjani (Endogami: Jurnal Ilmiah Kajian Antropologi, 2023)
Women and criminality. It sounds still unfamiliar to be side-by-side, however, that phenomenon is behind this study. At first, the women here were part of the wider community who had easy access to many things, they also had a crucial position in their families. Moving into prison causes many impacts, included culture shock. Conducted by using qualitative phenomenological methods with observation and in-depth interview as data collection techniques, this study aims to reveal the process that occurs in the journey of women prisoners at Lapas Perempuan Kelas IIA Semarang who have different status in their families including single women, housewives and single mothers to achieve adaptation in prison. The results showed that the greater changes experienced by women prisoners before and after being in prison, the more complex their social adaptation process in facing the new environment there. In prison, they live within limits, deprived of the right to determine everything according to their own wishes. However, social demands push women prisoners to adapt immediately, because otherwise conditions will get worse and they can be eliminated from their own environment. This social adaptation is achieved gradually, through several phases and includes various aspects such as acceptance of themselves, other elements contained in prison, as well as elements in their original lives including friends, neighbors and family.